Rotor Speed and Stator Resistance Identification Scheme for Sensorless Induction Motor Drives - Zicheng Li; Zhouping Yin; Youlun Xiong; Xinzhi Liu (Institute of Advanced Engineering and Science, 2013)
This paper proposes a rotor speed identification method for sensorless induction motor drives based on a model reference adaptive system (MRAS). In this scheme, the error between estimated stator current and real stator current is regarded as the system error to estimate the rotor speed. Adaptive full-order flux observers for estimating the rotor speed are developed using Lyapunov’s stability theory. The stator resistance identification algorithm is developed with rotor speed estimating method in a systematic manner. Because of the stator resistance varies with inner temperature of the motor, the influence of motor speed estimation due to stator resistance identification error is analyzed. The error compensation method for stator resistance estimation is also proposed. Simulation and experimental results show the good performance for the proposed scheme in speed and robustness for sensorless induction motor drives. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1865